2019
DOI: 10.1111/hdi.12740
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation vs. parathyroidectomy for secondary hyperparathyroidism in maintenance hemodialysis patients

Abstract: Introduction: Secondary hyperparathyroidism (SHPT) is a serious and common problem in patients undergoing maintenance hemodialysis. Minimally invasive microwave ablation (MWA) has been used to treat SHPT and shows some advantages. However, its efficacy is still undefined. The primary purpose of this study was to determine the efficacy and safety of MWA compared to total parathyroidectomy plus forearm autotransplantation. Methods: The SHPT patients who were undergoing maintenance hemodialysis (follow‐up for 6 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…The studies covered a period !8 years, from 2009 to 2017. Two were retrospective cohort studies [26,27], and six were retrospective self-control studies [28][29][30][31][32][33]. The mean follow-up period ranged from six to 23 months, and the sample size ranged from 9-56 patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies covered a period !8 years, from 2009 to 2017. Two were retrospective cohort studies [26,27], and six were retrospective self-control studies [28][29][30][31][32][33]. The mean follow-up period ranged from six to 23 months, and the sample size ranged from 9-56 patients.…”
Section: Discussionmentioning
confidence: 99%
“…All studies included in the meta-analysis reported calcium measurements obtained before MWA. Five articles reported calcium levels as measured one day after MWA [27,28,[30][31][32].…”
Section: The Change Of Calciummentioning
confidence: 99%
See 2 more Smart Citations
“…According to the previous studies, the incidence of postoperative SH in SHPT patients ranges from 37% to 57% and potential clinical parameters (eg, preoperative serum iPTH, calcium, and pruritus) associated with the occurrence of SH after PTX have been identified . Hypocalcemia was also common in 38.3% to 45.5% SHPT patients after MWA treatment . However, there has been no such study to systematically evaluate the risk factors associated with SH after MWA.…”
Section: Introductionmentioning
confidence: 99%